Życie w dolinach. Dzieje Świerzawy i okolic - Ruchniewicz, Małgorzata; Wiszewski, Przemysław (Publishing House eBooki.com.pl, 2015)
The book tells the story about the past of local community living inside the borders of Świerzawa municipality in the valley of the river Kaczawa (Katzbach) in Lower Silesia. The current settlement network was founded between the mid-thirteenth and mid-fourteenth centuries, when as a result of a colonization movement initiated by the Silesian princes, new settlements were brought to life. The first sources that mention the town date back to the mid-fourteenth century. The city was highly dependent on the surrounding knighthood – von Zedlitz, von Redern, von Hochberg families. During the 16th century the sense of the local community was strengthened by the widespread adoption of a new confession – Lutheranism. It is not clear to what extent the local settlements were affected by the Thirty Years’ War. In general the area renewed its economic potential after the war relatively quickly. The community was dominated by representatives of the middle-class nobility, and the town was only a supplement to the almost independently operating noble estates. The period of Świerzawa belonging to Prussia changed little in the situation of the town. It remained a small center of craft and merchant life that served its residents and customers from nearby villages. The years 1914–1945 in the history of Świerzawa were extremely dynamic and dramatic. The human, economic and political costs of World War I, the fall of the empire and the economic crisis with hyperinflation shook the foundations of existence of such a small community as the one in Świerzawa. In the early 1930’s support for the Nazis was rapidly growing. Adolf Hitler was made an honorary citizen of the town in March 1933. The second half of the 20th century brought Świerzawa many tumultuous changes. The fruit of the war and political decisions of the Allies were to change the eastern border of Germany, and reconstruct the national structure of the lands joined to Poland. The situation of the town was also strongly influenced by the policy of the government which implemented the reconstruction of the system based on Soviet patterns. Economic life under the banner of the liquidation of capitalism was subjected to topdown control and inspection, eliminating private entrepreneurship. Świerzawa remained a small municipal centre but it managed to recover its city charter towards the end of the communist era. During the Third Republic of Poland (after 1989) an important phenomenon was the development of the local self-government. Social life develops, and residents create many different organizations and companies. There is a growing interest in the history of the city and its region, and historical heritage is properly taken care of.
Keywords: microhistory; long-term history; economy; social history; social cohesion; region; locality; nobility; Silesia; Świerzawa; the Sudetes (Sudety Mountains); Sudetes’ Foothills